Impact of the COVID-19 Pandemic on Children and Adolescents with New-Onset Type 1 Diabetes - Kamrath, Clemens; Eckert, Alexander J.; Holl, Reinhard W.; Rosenbauer, Joachim; Justus Liebig University Giessen (My University, 2023)
Background: The COVID-19 pandemic has an impact on the incidence of type 1 diabetes and frequency of diabetic ketoacidosis. However, the exact relationships are unclear. It is also not known whether this is a short-term phenomenon or whether the effects have long-term relevance. Furthermore, it is not known whether these changes during the pandemic are due to direct effects of SARS-CoV-2 or to changes in the patient’s environment during the pandemic. Methods: We conducted an extensive literature search on PubMed. For the estimation of relative risks of new-onset type 1 diabetes, we applied a Poisson regression model and for the comparison of incidences and we included the logarithm of person-years. Furthermore, we performed a meta-analysis using the logarithm of the relative risk for new-onset type 1 diabetes as effect size. Results: Pooling the relative risk estimates in a random-effects meta-analysis revealed that the type 1 diabetes incidence rate increased by 20% (relative risk 1.200 (95% CI 1.125, 1.281)), and that the risk of new-onset type 1 diabetes after a SARS-CoV-2 infection increased by 62% (relative risk 1.622 (95% CI 1.347, 1.953)) compared with the prepandemic period. Conclusion: There is considerable evidence that there is an increase in type 1 diabetes in children during the COVID-19 pandemic. Many studies suggesting a direct effect of SARS-CoV-2 have methodological weaknesses. As no evidence of an increase in presymptomatic cases with isolated islet autoimmunity was found, this could also suggest an accelerated transition from presymptomatic patients to clinically overt type 1 diabetes. Furthermore, there was a marked exacerbation of the preexisting increase in the prevalence of diabetic ketoacidosis at diagnosis of type 1 diabetes during the pandemic. Both the increased incidence of paediatric type 1 diabetes and the higher prevalence of diabetic ketoacidosis at diagnosis led to a massive rise in the number of children with diabetic ketoacidosis during the pandemic.
Keywords: ddc:610